PS 02-24 INCREMENTAL IMPACT OF BLOOD PRESSURE ON CORONARY CALCIFICATION AND ATHEROSCLEROSIS IN ASYMPTOMATIC INDIVIDUALS: ANALYSIS FROM CORONARY COMPUTED TOMOGRAPHIC ANGIOGRAPHY REGISTRY. (September 2016) - Choi, Ik Jun; Hwang, Byung-Hee; Seo, Suk Min; Koh, Yoon-Seok; Chung, Woo-Baek; Park, Hun-Jun; Kim, Pum-Joon; Ihm, Sang-Hyun; Chang, Kiyuk; Jeon, Doo-Soo; Chung, Wook-Sung
Abstract : Objective: The aim of this study was to assess the level of blood pressure on the extent and developmental pattern of coronary artery disease (CAD). Design and Method: A total of 2, 676 self-referred asymptomatic individuals without known CAD who underwent 64-channel dual-source coronary computed tomography angiography (CCTA) between 2006 and 2010. The patients were divided into three groups based on their systolic blood pressure (group 1 <120mmHg, group 2 120∼139mmHg, and group 3 ≥140mmHg). We compared the coronary artery calcium score (CACS), atheroma burden obstructive score (ABOS), segment involvement score (SIS), and segment stenosis score (SSS). All-cause mortality during 3 years was also compared. Results: Patients with higher blood pressure possessed greater degree of CACS, ABOS, SIS, and SSS (p<0.001 for all) with associated with higher all-cause mortality (log rank, p = 0.002). Conclusions: In asymptomatic individuals, normal blood pressure is associated with a lower extent and severity of coronary calcium and atherosclerosis as well as risk of mortality.